A New Energy‐Saving Catalytic System: Carbon Dioxide Activation by a Metal/Carbon Catalyst. Issue 18 (12th September 2017) - Yun, Danim; Park, Dae Sung; Lee, Kyung Rok; Yun, Yang Sik; Kim, Tae Yong; Park, Hongseok; Lee, Hyunjoo; Yi, Jongheop
Abstract: The conversion of CO2 into useful chemicals is an attractive method to reduce greenhouse gas emissions and to produce sustainable chemicals. However, the thermodynamic stability of CO2 means that a lot of energy is required for its conversion into chemicals. Here, we suggest a new catalytic system with an alternative heating system that allows minimal energy consumption during CO2 conversion. In this system, electrical energy is transferred as heat energy to the carbon‐supported metal catalyst. Fast ramping rates allow high operating temperatures ( T app =250 °C) to be reached within 5 min, which leads to an 80‐fold decrease of energy consumption in methane reforming using CO2 (DRM). In addition, the consumed energy normalized by time during the DRM reaction in this current‐assisted catalysis is sixfold lower (11.0 kJ min −1 ) than that in conventional heating systems (68.4 kJ min −1 ). Abstract : Hot current : We describe a new catalytic system for highly energy‐efficient CO2 activation. The system is designed so that the catalyst bed is exposed to an electron flow in a modified reactor, and heat energy to activate CO2 molecules is generated from the interface of the metal catalysts and conductive carbon. In this system, the interface of the active metals plays the role of a nanoreactor, which minimizes energy loss.